Biopesticide and bioagents in integrated insect pest managemet of mango - Srivastava R.P; Srivastava R.P. (Luknow Anil printing press, 1997)
the taditionally use of insecticides has been main mode of control the access use of pesticides resulted in serious environmental problems
mango hopper fruit flies coccids gall midges
Keywords: mango hopper,fruit flies,coccides